2020
DOI: 10.1093/ndt/gfaa298
|View full text |Cite
|
Sign up to set email alerts
|

Urinary mulberry bodies as a potential biomarker for early diagnosis and efficacy assessment of enzyme replacement therapy in Fabry nephropathy

Abstract: Background The inability of enzyme replacement therapy (ERT) to prevent progression of Fabry nephropathy (FN) in the presence of >1 g/day proteinuria underscores the necessity of identifying effective biomarkers for early diagnosis of FN preceding proteinuria. Here we attempted to identify biomarkers for early detection of FN. Methods Fifty-one Fabry disease (FD) patients were enrolled. Urinary mulberry bodies (uMBs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…uMBs, which are observed in the urine by light microscopy as laminated bodies with a whorled shape, are a speci c nding in FD. uMBs originate from mainly podocytes that have accumulated GL3 and are detected before proteinuria develops [37][38][39]. In previous report, high renal pathological score was observed in female patients with only uMBs without albuminuria [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uMBs, which are observed in the urine by light microscopy as laminated bodies with a whorled shape, are a speci c nding in FD. uMBs originate from mainly podocytes that have accumulated GL3 and are detected before proteinuria develops [37][38][39]. In previous report, high renal pathological score was observed in female patients with only uMBs without albuminuria [40].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that uMBs are potential early biomarkers of renal injury. Furthermore, a recent study showed that degree of uMBs excretion correlated with podocyte vacuolation and ERT reduces uMBs excretion [39,41]. Podocyturia has also been reported as an early marker of renal injury, but detection requires staining [42].…”
Section: Discussionmentioning
confidence: 99%
“…Selvarajah et al reported that the sensitivity and specificity of these tests were 97.1% and 100%, respectively, in 35 patients with FD and 21 controls with other renal diseases [ 12 ]. In contrast, Yonishi et al reported a relatively lower positivity ratio and showed that 32 of the 51 (62.7%) patients with FD were positive for MBs/MCs [ 13 ]. Here, we evaluated the accuracy of MBs/MCs testing in FD patients and found that these tests have high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Mulberry bodies (MBs) are the characteristic fatty components of urinary sediments that appear as whorled laminated bodies, while mulberry cells (MCs) are distal tubular epithelial cells loaded with MBs [ 9 ]. Although the detection of urinary MBs or MCs can aid in the early diagnosis of FD [ 10 , 11 ], few studies have evaluated the accuracy of this diagnostic method [ 12 , 13 ]. Moreover, whether MBs/MCs can be detected in the urine of patients at different stages of FD, heterozygous females, and asymptomatic GLA variant carriers remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the presence of urinary mulberry cells (MCs) and mulberry bodies (MBs) has been researched as an early diagnosis of FD. Urinary MCs and MBs are characteristic features of Fabry disease, being released from epithelial cells or podocytes with Gb-3 accumulation, reflecting the podocyte injury (SHIMOHATA et al, 2017;YONISHI et al, 2022). MBs can be distinguished from fat particles by their inner lamellar appearance (Shimohata et al, 2017).…”
Section: Diagnosismentioning
confidence: 99%